New-onset left bundle branch block after transcatheter aortic valve replacement is associated with adverse long-term clinical outcomes in intermediate-risk patients: an analysis from the PARTNER II trial. (23rd April 2019) - Nazif, Tamim M; Chen, Shmuel; George, Isaac; Dizon, Jose M; Hahn, Rebecca T; Crowley, Aaron; Alu, Maria C; Babaliaros, Vasilis; Thourani, Vinod H; Herrmann, Howard C; Smalling, Richard W; Brown, David L; et al.
Abstract: Aims: Transcatheter aortic valve replacement (TAVR) is now an established therapy for intermediate-risk surgical candidates with symptomatic, severe aortic stenosis. The clinical impact of new-onset left bundle branch block (LBBB) after TAVR remains controversial and has not been studied in intermediate-risk patients. We therefore sought to analyse outcomes associated with new LBBB in a large cohort of intermediate-risk patients treated with TAVR. Methods and results: A total of 2043 patients underwent TAVR in the PARTNER II trial and S3 intermediate-risk registry and survived to hospital discharge. Patients were excluded from the current analysis due to baseline conduction disturbances, pre-existing permanent pacemaker (PPM), and new PPM during the index hospitalization. Clinical outcomes at 2 years were compared between patients with and without persistent, new-onset LBBB at hospital discharge, and multivariable analysis was performed to identify predictors of mortality. Among 1179 intermediate-risk patients, new-onset LBBB at discharge occurred in 179 patients (15.2%). Patients with new LBBB were similar to those without except for more frequent diabetes and more frequent treatment with SAPIEN 3 vs. SAPIEN XT. At 2 years, new LBBB was associated with increased rates of all-cause mortality (19.3% vs. 10.8%, P  = 0.002), cardiovascular mortality (16.2% vs. 6.5%, P  < 0.001), rehospitalization, and new PPM implantation. By multivariable analysis, new LBBB remained an independent predictor of 2-year all-cause [hazard ratio (HR) 1.98, 95% confidence interval (95% CI) 1.33, 2.96; P  < 0.001] and cardiovascular (HR 2.66 95% CI 1.67, 4.24; P  < 0.001) mortality. New LBBB was also associated with worse left ventricular systolic function at 1 and 2-year follow-up. Conclusions: In a large cohort of intermediate-risk patients from the PARTNER II trial and registry, persistent, new-onset LBBB occurred in 15.2% of patients without baseline conduction disturbances or pacemaker. New LBBB was associated with adverse clinical outcomes at 2 years, including all-cause and cardiovascular mortality, rehospitalization, new pacemaker implantation, and worsened left ventricular systolic function. Clinical Trial Registration: ClinicalTrials.gov #NCT01314313 and NCT03222128.